Allogeneic bone marrow transplantation with post-transplant cyclophosphamide for patients with HIV and haematological malignancies: a feasibility study. Issue 9 (September 2020) - Durand, Christine M; Capoferri, Adam A; Redd, Andrew D; Zahurak, Marianna; Rosenbloom, Daniel I S; Cash, Ayla; Avery, Robin K; Bolaños-Meade, Javier; Bollard, Catherine M; Bullen, C Korin; Flexner, Charles; Fuchs, Ephraim J; et al.
Summary: Background: Allogeneic blood or marrow transplantation (alloBMT) is a potentially life-saving treatment for individuals with HIV and haematological malignancies; challenges include identifying donors and maintaining antiretroviral therapy (ART). The objectives of our study were to investigate interventions to expand donor options and to prevent ART interruptions for patients with HIV in need of alloBMT. Methods: This single-arm, interventional trial took place at the Johns Hopkins Sidney Kimmel Comprehensive Cancer Center (Baltimore, MD, USA). Individuals with HIV who were at least 18 years of age and referred for alloBMT for a standard clinical indication were eligible. The only exclusion criterion was a history of documented resistance to enfuvirtide. We used post-transplant cyclophosphamide as graft-versus-host disease (GVHD) prophylaxis to expand donor options and an optimised ART strategy of avoiding pharmacoenhancers and adding subcutaneous enfuvirtide during post-transplant cyclophosphamide and during oral medication intolerance. Our primary outcome was the proportion of participants who maintained ART through day 60 after alloBMT. We measured the HIV latent reservoir using a quantitative viral outgrowth assay. This study is registered on ClinicalTrials.gov, NCT01836068 . Findings: Between June 1, 2013, and August 27, 2015, nine patients who were referred for transplant provided consent. Two patients had relapsed malignancy before donor searches were initiated. Seven patients had suitable donors identified (two matched sibling, two matched unrelated, two haploidentical, and one single-antigen mismatched unrelated) and proceeded to alloBMT. All patients maintained ART through day 60 and required ART changes (median 1, range 1–3) in the first 90 days. One patient stopped ART and developed HIV rebound with grade 4 meningoencephalitis at day 146. Among six patients who underwent alloBMT and had longitudinal measurements available, the HIV latent reservoir was not detected post-alloBMT in four patients with more than 95% donor chimerism, consistent with a 2·06–2·54 log10 reduction in the HIV latent reservoir. In the two patients with less than 95% donor chimerism, the HIV latent reservoir remained stable. Interpretation: By using post-transplant cyclophosphamide as GVHD prophylaxis, we successfully expanded alloBMT donor options for patients with HIV. Continuing ART with a regimen that includes enfuvirtide post-alloBMT was safe, but life-threatening viral rebound can occur with ART interruption. Funding: amfAR (the Foundation for AIDS Research), Johns Hopkins University Center for AIDS Research, and National Cancer Institute.